The Mechanism of the Effects of Experiential Marketing on Urban Consumers' Well-Being. (15th October 2020) - Liu, Hongshen; Fu, Yuying; He, Hao
Abstract : Knowing how to improve urban consumers' well-being is of great importance for sustainable urban development and has become a research hotspot in the field of service marketing, which is evolving from functionality-focused view into experience-focused view. This study explored the mechanism and boundary conditions of experiential marketing on urban consumers' well-being with a survey data collected from 256 consumers in the catering service industry in China. The results showed that experiential marketing had a significant positive impact on consumer well-being, experiential value played a partial mediation role between experiential marketing and consumer well-being, value proposition engagement moderated the relationship between experiential value and consumer well-being, and value proposition engagement moderated the mediation role of experiential value between experiential marketing and consumer well-being. This study complements the literature of transformative service by revealing a complex mechanism relating to the effects of experiential marketing on urban consumers' well-being and provides theoretical guidance for service enterprises to improve their offerings.